Cybersecurity issues in space activities: international legal and technological aspects - Hordeiuk, A. O.; Demura, R. I. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
In this article, the authors have examined the current problems of ensuring legal regulation of cybersecurity of space activities on the international level in the minds of the growing dependence of humanity on satellite technologies. Real examples of cyberattacks on space infrastructure are given (in particular, incidents involving Landsat-7, Terra AM-1 satellites and the Viasat network), the negative consequences of which necessitate the construction of an effective international legal mechanism capable of contributing to the prevention and counteraction of cybercrime in the space industry. In order to create a powerful system of technological and legal protection of satellite space technologies, modern approaches of leading space powers (the USA, the EU, France, Germany, and the UK) to solving this problem were analyzed. It has been established that these approaches are reflected in the development of industry guidelines, approved practices for ensuring cybersecurity in the space segment by creating a comprehensive space cybersecurity system, which operates, for example, in EU countries. Within this system, risk and threat analysis is carried out, information flows and technical parameters are monitored, which allows for preventive detection of cyber incidents and implementation of cyber security measures for space infrastructure. In the EU countries, the following are working quite effectively: the Federal Office for Information Security (BSI) in Germany, one of whose options is to manage space cybersecurity; the French Cybersecurity Agency (ANSSI), which is responsible for protecting military satellites, detecting cyberattacks, and restoring infrastructure after damage caused by them. It is noted that space powers are cooperating in the Olympic Defender space program to strengthen defense and deter hostility in outer space. Based on the analysis of the experience of space powers in the legal regulation of cybersecurity of space activities (in particular, satellite systems), in order to build an effective international legal mechanism for ensuring cybersecurity in this area with a justification of feasibility, the authors proposed: the creation of an international convention on cybersecurity of space activities and an specialized international organization as a monitoring and control body, as well as a platform for rulemaking activities; the development of unified international space security standards, including cybersecurity standards; in the context of active commercialization of space activities, establishing protocols for compliance with cybersecurity measures for privet companies and providing algorithms and methods for testing satellite systems in order to identify possible gaps and prevent cyberattacks. Particular attention is paid to the proposal to use blockchain technology and the introduction of the bug bounty concept as innovative tools in the field of cyber defense.